1993
DOI: 10.1172/jci116659
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin-M stimulates tyrosine protein phosphorylation in parallel with the activation of p42MAPK/ERK-2 in Kaposi's cells. Evidence that this pathway is important in Kaposi cell growth.

Abstract: Oncostatin-M (OSM) is a potent mitogen for Kaposi's sarcoma (KS) cells. We studied signaling by the OSM receptor in three AIDS-related KS lines and show induction of tyrosine phosphorylation of 145-, 120-, 85-, and 42-kD substrates. The 42-kD substrate was identified as p42MAPK (mitogen-activated protein kinase), also known as ERK-2. This serine/threonine kinase relays mitogenic signals from receptor tyrosine protein kinases (TPKs) or receptor-associated TPKs to transcriptional activators. The OSM dose depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 43 publications
1
28
1
Order By: Relevance
“…This suggests that endogenous IL-6 synthesis is not directly involved in the OSM-induced mitogenic response of dermal fibroblasts. OSM belongs to a family of cytokines that utilize the Janus kinase (JAK)-STAT signaling pathway (40) and MAP kinase pathway (34). Indeed, it has been reported recently that OSM activates STAT1 and STAT3 in human dermal fibroblasts (21,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that endogenous IL-6 synthesis is not directly involved in the OSM-induced mitogenic response of dermal fibroblasts. OSM belongs to a family of cytokines that utilize the Janus kinase (JAK)-STAT signaling pathway (40) and MAP kinase pathway (34). Indeed, it has been reported recently that OSM activates STAT1 and STAT3 in human dermal fibroblasts (21,41).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that OSM stimulated tyrosine phosphorylation in various types of cells (34). Therefore, we investigated the effects of tyrosine kinase inhibitor on OSM-induced dermal fibroblast DNA synthesis.…”
Section: The Effect Of Tyrosine Kinase Inhibitor On Osm-induced Dermamentioning
confidence: 97%
“…OSM belongs to a family of cytokines that utilize the JAK-STAT signaling pathway (10), but OSM activation of other signaling pathways such as mitogen-activated protein kinase has also been observed (35). Indeed, it has been reported recently that OSM stimulates the MMP-1 (interstitial collagen- 1-7) or the mutant probe (same promoter fragment containing a substitution mutation in the proximal TCC motif between bp Ϫ128 and Ϫ126; see ase) gene through AP-1 and STAT response elements that act synergistically (27).…”
Section: Discussionmentioning
confidence: 99%
“…This is a 10-to 20-fold greater expression of these receptors compared to other cell types (9,10), and is especially significant when compared to the estimated 650 TNF receptors expressed by endothelial cells (2,9). Second, endothelial cells respond to oncostatin M with activation of MAP kinase activity (11), IL-6 secretion (9), and delayed, but prolonged, P-selectin synthesis (12). Third, oncostatin M is the major autocrine growth factor for Kaposi's sarcoma cells (13), and these spindle-shaped cells are thought to be of endothelial cell origin (14,15).…”
Section: Introductionmentioning
confidence: 99%